Mass Media Role in Spreading the Sports for All Culture among Female University Students in the Sultanate of Oman in the Light of Oman Vision 2040 - gaafar, amin; Al-Hadabi, Badriya (Journal of Physical Education, 2023)
The research aims to identify the mass media role in spreading sports culture among women in the Sultanate of Oman in the light of Oman Vision 2040. The descriptive method using the survey way was used. The survey was conducted on a pilot sample of (25) examinees during the period from 2-15 December 2020, and it was conducted on the (84) research main sample members, between December 20/2020 to February 1/ 2021. The results indicated that the mass media focused on the importance of practicing all aspects of sports for all activities in terms of the positive effects on their physical, psychological and social health. The study recommends that sports media should rely on academic experiences to convey their ideas about the importance of women exercising.